A systematic Literature Review: Technology Digital and ESG - Rahmi Syafitri; Noorlailie Soewarno (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: This study aims to analyze the relationship between digital technology and ESG performance using the Systematic Literature Review (SLR) method from previous studies in the last decade. Background Problems: This convergence of technological innovation, ESG performance, and responsive policies creates a new business paradigm. However, understanding the impact of digital technology on ESG performance remains limited. Novelty: this article is to explore the relationship between digital technologies and ESG, thereby providing a state-of-the-art research overview on the topic. Research Methods: This research adopted the systematic literature review (SLR) methodology to examine the influence of digital technology on ESG performance in the last 10 years (2015-2025) from leading international databases. The SLR process involved three main stages: planning the review, applying screening criteria, and analyzing the review. Finding/Results: Over the past decade, research on digital technology and ESG has shown a positive impact on performance, particularly in the face of global challenges like COVID-19. Technologies like Industry 5.0, green innovation, and digital inclusive finance strengthen ESG reporting. The Stakeholder Theory is widely used, emphasizing stakeholder interests in sustainable decision-making. Conclusion: Future studies on how digital technology affects ESG performance ought to incorporate viewpoints from a variety of stakeholders, such as investors, customers, and legislators. The AIESG Protocol can encourage transparency, and dual materiality can improve ESG performance. Investment in digital infrastructure and qualitative methods must be combined for post-pandemic adaption.